2021
DOI: 10.15446/rfnam.v74n1.89032
|View full text |Cite
|
Sign up to set email alerts
|

Digitaria insularis control by using herbicide mixtures application in soybean pre-emergence

Abstract: Sourgrass (Digitaria insularis) is one of the main weeds in the soybean crop. In order to control its growth, an increase of herbicide rates is required to simplify its management as it a plant with high vegetative capacity and seed production. It implies to select the herbicide-resistent Digitaria insularis biotypes. Nevertheless, some information is still contrasting the antagonist of synthetic auxinic herbicides, associated with glyphosate and ACCase inhibitors mixtures, for the control of weeds resistant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The synergism of glyphosate and triclopyr have been observed on different weed species [ 20 , 33 , 70 ]. In addition, the synergism of glyphosate and other auxin mimic/synthetic auxin have been reported in various weeds management practices [ 55 , [71] , [72] , [73] ]. On the other hand, the efficacy of the mixture of glyphosate plus triclopyr was found to be at par with the efficacy of a single glyphosate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergism of glyphosate and triclopyr have been observed on different weed species [ 20 , 33 , 70 ]. In addition, the synergism of glyphosate and other auxin mimic/synthetic auxin have been reported in various weeds management practices [ 55 , [71] , [72] , [73] ]. On the other hand, the efficacy of the mixture of glyphosate plus triclopyr was found to be at par with the efficacy of a single glyphosate.…”
Section: Discussionmentioning
confidence: 99%
“…Opoku-ameyaw et al [ 52 ], reported the regrowth of weeds after three to four months of double herbicide application. Bauer et al [ 71 ], described a single application of herbicides as influencing early regrowth of certain weeds including Digitaria insularis. Growing of leguminous plants such as Mucuna shows low residual effect of herbicides and soil fertility due to low intra-weed competition [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, GS seedlings over 45 days old, which have begun to tiller and clump together, also become difficult to control (Andrade Jr et al, 2018). Clethodim, fluazifop-p-buthy, tepraloxydim, clethodim, fenoxaprop-P-methyl, paraquat, haloxifop-P-methyl and imazapyr, when tested on sourgrass plants with up to two tillers, have demonstrated control levels exceeding 90% (Bauer et al, 2021;Correia et al, 2012;Correia et al, 2009;Zobiole et al, 2016;Barroso et al, 2014;Petter et al, 2015). However, once the plant has formed clumps and developed numerous propagation structures, control efficacy decreases to approximately 50% due to regrowth (Procópio et al, 2006).…”
Section: Management Methods Of Sourgrassmentioning
confidence: 99%
“…The problem is exacerbated when sourgrass exhibits glyphosate resistance, as GR plants do not incur fitness penalties compared to glyphosatesusceptible (GS) plants (Martins et al, 2017;Pereira et al, 2017). These characteristics collectively make the control of sourgrass very challenging (Bauer et al, 2021).…”
Section: Negative Impacts Of Sourgrass On Agriculturementioning
confidence: 99%
“…The low performance of combinations of herbicides with an immediate contact effect, such as diquat, with systemic herbicides, has been reported (Wehtje et al, 2008). In addition, there is antagonism between ACCase inhibitors and synthetic auxins (Underwood et al, 2016;Webster et al, 2019;Bauer et al, 2021) or between ACCase inhibitors and ALS inhibitors.…”
Section: Andropogon Bicornismentioning
confidence: 99%